Pomiar ryzyka kredytowego przedsiębiorstwa - Kuziak, Katarzyna (Enterprise Credit Risk Measurement, 2007)
In the paper credit risk measurement based on the enterprise value distribution was presented. Estimation of probability density function was perform by use Black-Scholes-Merton option pricing model. Sensitivity analysis of probability of default in the option pricing model was given. Two example of estimation probability of default for enterprises coming from two sectors (media and telecommunication) listed on Warsaw Stock Exchange illustrated problems of the credit risk measurement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 100-107